Differential Effects of Reconstituted High-density Lipoprotein on Coagulation, Fibrinolysis and Platelet Activation during Human Endotoxemia - Pajkrt, Dasja; Lerch, Peter G; van der Poll, Tom; Levi, Marcel; Illi, Marlies; Doran, Jan E; Arnet, Beat; van den Ende, Abraham; ten Cate, Jan Wouter; van Deventer, Sander J H (Thrombosis and Haemostasis, 1997)
High-density lipoproteins (HDL) can bind and neutralize lipopoly- saccharides (LPS) in vitro and in vivo. HDL can also affect fibrinolytic activity and can directly influence platelet function by reducing platelet aggregation. In this study, the effects of reconstituted HDL (rHDL) on LPS-induced coagulation, fibrinolysis and platelet activation in humans were investigated. In a double-blind, randomized, placebo-controlled, cross-over study, eight healthy male volunteers were injected with LPS (4 ng/kg) on two occasions, once in conjunction with rHDL (40 mg/kg, given as a 4 h infusion starting 3.5 h prior to LPS injection), and once in conjunction with placebo. rHDL significantly reduced LPS-induced activation of coagulation (plasma levels of prothrombin fragment F1+2) and fibrinolysis (plasma levels of tissue type plasminogen activator antigen, t-PA). No effect was observed on LPS-induced inhibition of the fibrinolytic pathway (PAI-1) or on the transient thrombocytopenia elicited by LPS. Furthermore, rHDL treatment significantly enhanced the inhibition of collagen-stimulated inhibition of platelet aggregation during endotoxemia, but had no such effect on arachido- nate-stimulated platelet aggregation. rHDL treatment per se also reduced collagen-induced platelet aggregation. These results indicate that rHDL modifies the procoagulant state associated with endotoxemia.